TINDAK TUTUR DALAM WACANA RESEP MASAKAN ASYHA AL-ALAWIYYAT KARYA KAUSAR AL-ADHAM ISMAâIL: ANALISIS PRAGMATIK - , ZAINURRAKHMAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research regarding a study of speech act in recipes of Asyha> al- H}alawiyya>t by Kausar al-Adham Isma> 'i>l is conducted because in the author not only using command line mode, but also the mode of declarative sentences. The purpose of this research is to describe the types of speech acts uttered by the author of Asyha> al-H}alawiyya>t recipe with pragmatics analysis. The method applied in this study is pragmatic-comparative method, a method in which the determining tool is the audience or the reader. Based on the analysis, it was found that in functional aspect of the sentence in the Asyha> al-H}alawiyya>t, there are two types of speech acts: illocutionary and perlocutionary act. Locutionary act is not found in this study because the sentences in the recipes are not intended to give any particular information, but order and predispose the subject to follow the ways of cooking explained strictly. Illocutionary act in this study consists of assertive and directive act. Based on sentence mode, there are five types of speech acts found in this recipe: direct speech act, indirect speech act, literal speech act, direct literal speech act, and indirect literal speech act.